Effect of nitrogen sources on yield and yield components of potato (Solanum tuberosum) cultivars - VENKATASALAM, E P; BAIRWA, AARTI; L, DIVYA K; SUDHA, R; MHATRE, PRIYANK H; GOVINDAKRISHNAN, P M; SINGH, R K (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted during two consecutive summer seasons to evaluate the effect of nitrogen sources on yield and yield attributing characters of potato (Solanum tuberosum L.) cultivars. The experiment was laid out in a factorial randomized block design with four potato cultivars and three different nitrogen sources. The sources of phosphorous (P) and potash (K) were single super phosphate (SSP) and muriate of potash (MOP) respectively where the nitrogen (N) source is urea and di-ammonium-phosphate. In case of di-ammonium phosphate (DAP) it served source for both N and P. The pooled analysis showed significant difference between cultivars, nitrogen sources andits interactions on all characters studied. Our results revealed that application of recommended dose of N in the form of urea in both basal as well as top dressing significantly increased the vegetative growth. However, N 75% supplied in the form of DAP as basal and remaining nitrogen 25% in the form of ammonium sulphate as top dressing (T7)along with recommended dose of P and K and N 75% supplied in the form of ammonium sulphate as basal and 25%as top dressing (T2) along with recommended P and K resulted maximum marketable tuber yield in terms of tubernumber as well as weight. Therefore, for maximizing the marketable tuber yield N can be applied in the form of DAPand ammonium sulphate.